Removal of phosphorous and nitrogen from wastewater in Brachiaria-based constructed wetland. (October 2019) - Nandakumar, S.; Pipil, Harsh; Ray, Sanak; Haritash, A.K.
Abstract: Considering the prevalence of eutrophication of water bodies, sustainable treatment technologies like constructed wetlands (CWs) have come up as a promising alternate for nutrient removal and wastewater treatment. The present study was undertaken to investigate the potential of Brachiaria -based constructed wetland for removal of phosphorus and nitrogen in different seasons of a sub-tropical region. The CW cell could efficiently remove phosphate and nitrogen under varying influent concentrations across different seasons. Average removal of total phosphate increased from 55.2% (winter) to 78.5% (spring), 80.7% (autumn), and 85.6% (summer), and maximum removal rate was 384.4 mg/m2-day during the summer season. The soluble/available phosphate was removed on priority owing to its easy bio-availability. The removal efficiency of Brachiaria increased with increasing influent phosphate concentration (5–20 mg/l), if supplemented with nitrogen maintaining the N:P ratio of 5:1. This highlighted the characteristic of Brachiaria to absorb chemical shocks w.r.t. phosphate. The neutral pH (6.2–8.3) and oxidising conditions in rhizosphere ruled out possibility of binding of phosphate with cations (Ca, Fe, and Al) in sediments. Ambient temperature and sunshine hours regulated evapotranspiration and hence nutrient removal. Simultaneous removal of nitrogen (75.6–84.6%) by Brachiaria indicated that it can serve dual purpose of nutrient removal and fodder-production for livestock, thus serving as a sustainable prototype for rural communities in sub-tropical regions. Highlights: Brachiaria mutica efficiently removes phosphate and nitrogen under varying influent concentrations. Phosphorus removal is enhanced if nitrogen is amended with. Ambient temperature and sunshine hours regulated nutrient removal.